Reading Mandatory versus Reading for Pleasure: What Role Should the Spanish Teacher Assume? - Chinchilla Araya, Tatiana (2022)
The paper reflects on the new parameters of the reading approach in Costa Rican educational centers and the constant ministerial assertion that the student develops reading competence, from an approach that places the pleasure and enjoyment of the text over the obligation of said process. The above is done in light of the new approaches to the teaching of language and literature, as well as the scope and impact of the new study program for the subject of Spanish, from the Educational Policy "Ethics, aesthetics and citizenship", of the Ministry of Public Education of Costa Rica. It is up to the Spanish teacher to emphasize the value of reading as an integral process, not only for enjoyment and fun, but as a basic competence for the life of students in society, especially when considering the possibilities of access that exist today to many literary and non-literary works. It appeals to the importance of balancing the training of students who like reading activity, in the different literary and non-literary genres, with the development of people who are aware that reading is not just a space for "leisure, fun and pleasure", but a "necessary" ability to access knowledge, learn about other realities and function effectively in society, because although it is not always enjoyed, due to the diversity of topics and personal tastes, it cannot be an optional practice.